KEPATUHAN PENGELOLA E-WARONG (ELEKTRONIK WARUNG GOTONG ROYONG) DALAM MELAKSANAKAN PERATURAN MENTERI SOSIAL NOMOR 5 TAHUN 2021 DI KECAMATAN SUNGAYANG KABUPATEN TANAH DATAR - Ramla Husni; Nur Laila Meilani (CV. Adiba Aisha Amira, 2023)
This research is based on the Compliance of E-Warong (Electronic Warung Mutual Cooperation) Managers in Implementing the Minister of Social Affairs Regulation No. 5 of 2021 in Sungayang District, Tanah Datar Regency. Compliance is measured by the successful implementation of this basic food program with TKSK implementers, PKH assistants, E-Warong managers and beneficiary families. The purpose of this study was to find out the compliance of managers by looking at Ripley and Franklin's theory with a discussion of the level of compliance, no problems, and performance, as well as knowing the factors that influence the compliance of the basic food program in Sungayang District, Tanah Datar Regency. The method used in this study is a descriptive qualitative approach which describes the compliance of E-Warong managers in implementing social ministerial regulations in Sungayang District, Tanah Datar Regency. In addition, it is also to find out the factors that influence the compliance of E-Warong managers in implementing social minister regulations in Sungayang District, Tanah Datar Regency. The results of this study can be seen that compliance with the basic food program in Sungayang District, Tanah Datar Regency is seen by its compliance, there are no problems and performance has been carried out in accordance with Minister of Social Affairs Regulation No. 5 of 2021, but there are still some E-Warong managers who have not carried out their duties. Factors that influence compliance in implementing ministerial regulation no 5 of 2021 are human resources, socialization, technological developments. As a suggestion, E-Warongs in Sungayang sub-district should frequently conduct outreach to E-Warong managers about using the BRILink edition machine so that the use of E-Warongs will be more useful and the profits will be greater